2008
DOI: 10.1111/j.1749-8198.2008.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Mixed‐Income Housing Ameliorate Concentrated Poverty? The Significance of a Geographically Informed Sense of Community

Abstract: Since the 1990s, public policymakers have renewed support for mixed‐income housing development in low‐income neighborhoods as a means toward neighborhood revitalization and poverty amelioration. Research to date finds that, while mixed‐income developments in lower‐income neighborhoods have promoted area revitalization, they have accomplished less for people in these areas who live in poverty. This article focuses on mixed‐income projects that seek to de‐concentrate poverty in impoverished, urban neighborhoods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
(99 reference statements)
0
12
0
Order By: Relevance
“…A body of research has focused on how mixed income areas can have various positive consequences for the lower income households living in such neighborhoods, including possible improved social networks for job contacts leading to better employment outcomes, mental health benefits, increased self-esteem, and behavioral and health improvements for children (for a review of this literature see Levy, McDade, and Dumlao 2010). There are also proposed advantages for the neighborhood as a whole, including improved social control to address safety issues given that higher income residents might provide particular norms to increase safety (Fraser and Nelson 2008) or economic advantages by increasing market demand for higher-quality goods and services that can then be enjoyed by all residents (Levy, McDade, and Dumlao 2010). Nonetheless, there is also a possible long-term side effect in which income mixing brings about gentrification, which then can lead to increased income segregation over time, as was found in a study of rural settings (Golding 2015).…”
Section: How Mixing Can Help Neighborhood Dynamismmentioning
confidence: 99%
“…A body of research has focused on how mixed income areas can have various positive consequences for the lower income households living in such neighborhoods, including possible improved social networks for job contacts leading to better employment outcomes, mental health benefits, increased self-esteem, and behavioral and health improvements for children (for a review of this literature see Levy, McDade, and Dumlao 2010). There are also proposed advantages for the neighborhood as a whole, including improved social control to address safety issues given that higher income residents might provide particular norms to increase safety (Fraser and Nelson 2008) or economic advantages by increasing market demand for higher-quality goods and services that can then be enjoyed by all residents (Levy, McDade, and Dumlao 2010). Nonetheless, there is also a possible long-term side effect in which income mixing brings about gentrification, which then can lead to increased income segregation over time, as was found in a study of rural settings (Golding 2015).…”
Section: How Mixing Can Help Neighborhood Dynamismmentioning
confidence: 99%
“…2004a; Salama 1999). But questions remain – in Atlanta and elsewhere – as to how effective such public housing transformation initiatives have been at improving the housing and neighborhood conditions of relocated public housing residents (Fraser and Nelson 2008; Goetz 2009).…”
Section: The Poverty Deconcentration Imperative and Public Housing Trmentioning
confidence: 99%
“…Through these ongoing efforts, the AHA has gained a reputation as a leader in rethinking public housing by addressing its perceived failures and building on national housing-policy initiatives to deconcentrate poverty (Newman 2002;Oakley et al 2008;Popkin et al 2004a;Salama 1999). But questions remain -in Atlanta and elsewhere -as to how effective such public housing transformation initiatives have been at improving the housing and neighborhood conditions of relocated public housing residents (Fraser and Nelson 2008;Goetz 2009).…”
Section: The Poverty Deconcentration Imperative and Public Housing Trmentioning
confidence: 99%
“…Fraser and Nelson (2008) found that mixed income housing promoted neighborhood revitalization but did not meet the needs of lowerincome residents. They found that mixed income housing was successful in "lowering crime, improving economic indicators, and producing quality housing for market-rate and subsidized tenants…Yet, very low income residents faced barriers to self-sufficiency, health and general well-being" (p. 2141).…”
Section: Appraisal Of Hope VImentioning
confidence: 99%
“…Much of the research related to HOPE VI focuses on three areas: 1) challenges and possibilities of mixed income policy (Fraser and Nelson, 2008; GAO, 1998; HUD, 2003;Varady et al, 2005); 2) the impact of HOPE VI on residents (Popkin, 2007 GAO, 2003) and their children (Gallagher & Beata, 2007;Popkin et al, 2002); and 3) neighborhood and housing conditions as they relate to safety, amenities, and health (Goetz, 2010;Popkin et al, 2002, Rinker 2007.…”
Section: Appraisal Of Hope VImentioning
confidence: 99%